Corporate Criminal Liability On Criminal Actions in Consumer Protection - Fifid Bramita (Universitas Ahmad Dahlan, 2018)
The advancement of information technology affects the crime related to consumer protection. This impact is no longer confined to certain regions or country, but it is tranversing jurisdictional boundaries (transnational). Thus, the variety modes of the crime increase, not only used by individual, but also carried out by corporations. Criminalizing corporation is difficult, especially when related to consumer protection. That is because there are no legal provisions about corporate’s position and its responsibility in Criminal Law in Indonesia. Consequently, this condition leads to multi interpretations and thoughts between law enforcement officers. Therefore, it is necessary to have guidelines in handling crime cases done by companies. This study employs normative juridical research method. This research concludes that after the issuance of Indonesia’s Supreme Court Regulation Number 13 of 2016 About Procedures for Handling Criminal cases done by corporations, the law enforcement officers are no longer confused on how to handle the crime.Kata Kunci: Pertanggungjawaban Korporasi, Perlindungan Konsumen.